O slovenské „menšině" v Československém státě (1918-1938) - Barhoňová, Vladislava (Lidé města, 2000)
The paper deals with the question of relations between Czechs and Slovaks in the first, inter-war, Czechoslovak Republic (1918-1938). It is based on contemporary press, published in Bohemia and Slovakia. The basic question was a gradual political self-identification of Slovaks. It is presented by means of the attitudes of Hlinka's Slovak People's Party in 1923 (regional elections), the struggle for the rules of Slovak grammar (1933-rejection of their adaptation to the rules of Czech grammar), the Zvolen pact between the catholic Slovak People's Party anct the protestant Slovak National Party, the celebrations of the first Christian church in Slovakia (1933) and the declaration of Slovakia's autonomy (1938). To conclude: in 1918-1938, during the existence of the first Czechoslovak Republic, there was no Slovak minority. The first Czechoslovakia was de facto a multiethnic country, though officially it was designed as a country of Czechs and Slovaks, who had the will to create a single, Czechoslovak nation. The notion "minority" in the name of the paper is meant ironically and is to point to the approach often applied by Czechs for Slovaks.